NUEVOS REGISTROS DE HONGOS GASTEROIDES LEÑOSOS DESERTÍCOLAS (AGARICACEAE): BATTARREA STEVENII (LIBOSCHITZ) FR. Y CHLAMYDOPUS MEYENIANUS (KLOTZSCH) LLOYD, EN EL NORTE DE CHILE. (Boletín Micológico, 2016)
Battarrea stevenii (Liboschitz) Fr. and Chlamydopus meyenianus (Klotzsch) are two infrequently collected stalked gasteroid in Chile. They inhabit arid regions and emerge after early spring rains. New localities and descriptions are presented here.